The Role of Microfinance and Banking Services in Supporting Tourism-Based SMEs in Pematang Johar - Petrus Loo; Sipnarong Kanchawongpaisan; Muhammad Hafiz Abd Rashid; Phan Bao Giang; Suriani Suriani; Ridwan Nurdin; Nabilla Dwi Puspitasari (Eastasouth Journal of Positive Community Services, 2025)
Access to finance remains a critical challenge for rural Small, and Medium Enterprises (SMEs), especially those engaged in tourism-based economic activities. This community service project aimed to strengthen the financial literacy and banking inclusion of tourism-related SMEs in Pematang Johar Village, Deli Serdang Regency, Indonesia. The program introduced practical training on microfinance mechanisms, digital banking tools, and savings–loan schemes tailored to small entrepreneurs. The activity adopted a participatory service-learning approach involving 35 SMEs participants, local tourism operators, and village officials. The results demonstrated a 60% increase in participants’ understanding of microfinance systems, and 72% of participants opened new banking or digital wallet accounts after the training. The program shows that inclusive financial education and collaboration with local banking institutions can empower rural entrepreneurs and enhance the sustainability of tourism-based economic ecosystems.